Mass incarceration nation : how the United States became addicted to prisons and jails and how it can recover - Bellin, Jeffrey (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
The United States imprisons a higher proportion of its population than any other nation. Mass Incarceration Nation offers a novel, in-the-trenches perspective to explain the factors - historical, political, and institutional - that led to the current system of mass imprisonment. The book examines the causes and impacts of mass incarceration on both the political and criminal justice systems. With accessible language and straightforward statistical analysis, former prosecutor turned law professor Jeffrey Bellin provides a formula for reform to return to the low incarceration rates that characterized the United States prior to the 1970s.
Definition -- The deprivation of incarceration -- Where is mass incarceration? -- Distinguishing the criminal justice and criminal legal systems -- A crime surge -- Repeating patterns : crime, outrage, and harsher laws -- Legislating more punishment and less rehabilitation -- The futility of fighting crime with criminal law -- The role of race -- More police, different arrests -- Prosecutors turning arrests into convictions -- Judges turning convictions into incarceration -- Judicial interpretation -- Punishing repeat offenses -- The parole and probation to prison pipeline -- Disappearing pardons -- The mindlessness of jail -- What success looks like -- (Mostly) abolish the feds -- Less crime Part 1 : changing the rules -- Less crime Part 2 : decreased offending -- Reducing admissions and shortening stays -- Conclusion.
Title from publisher's bibliographic system (viewed on 03 Nov 2022).
Keywords: Criminal justice, Administration of -- United States; Imprisonment -- United States; Sentences (Criminal procedure) -- United States; Law reform -- United States